The Role of TonB Gene in Edwardsiella ictaluri Virulence - Abdelhamed, Hossam; Lawrence, Mark L.; Karsi, Attila (Frontiers in Physiology, 2017)
Edwardsiella ictaluri is a Gram-negative facultative intracellular pathogen that causes enteric septicemia in catfish (ESC). Stress factors including poor water quality, poor diet, rough handling, overcrowding, and water temperature fluctuations increase fish susceptibility to ESC. The TonB energy transducing system (TonB-ExbB-ExbD) and TonB-dependent transporters of Gram-negative bacteria support active transport of scarce resources including iron, an essential micronutrient for bacterial virulence. Deletion of the tonB gene attenuates virulence in several pathogenic bacteria. In the current study, the role of TonB (NT01EI_RS07425) in iron acquisition and E. ictaluri virulence were investigated. To accomplish this, the E. ictaluri tonB gene was in-frame deleted. Growth kinetics, iron utilization, and virulence of the EiΔtonB mutant were determined. Loss of TonB caused a significant reduction in bacterial growth in iron-depleted medium (p > 0.05). The EiΔtonB mutant grew similarly to wild-type E. ictaluri when ferric iron was added to the iron-depleted medium. The EiΔtonB mutant was significantly attenuated in catfish compared with the parent strain (21.69% vs. 46.91% mortality). Catfish surviving infection with EiΔtonB had significant protection against ESC compared with naïve fish (100% vs. 40.47% survival). These findings indicate that TonB participates in pathogenesis of ESC and is an important E. ictaluri virulence factor.